2018
DOI: 10.1017/s0954579418000755
|View full text |Cite
|
Sign up to set email alerts
|

What changes when? A reply to Beauchaine and Slep

Abstract: In their commentary, Beauchaine and Slep (2018) raise important issues regarding research on behavioral parenting training (BPT). In this reply we highlight key points of agreement and respond to issues that we feel require clarification. BPT has been repeatedly proven effective in decreasing disruptive child behavior (also in the work of our research team). Yet, there is much to learn about for whom and how BPT is effective. Specifically, assessing the how (i.e., mediation) comes with many challenges. One of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…This time point was analyzed because the interest was in changes in modeling and reinforcement which were expected immediately after the intervention rather than between post and follow-up measurements (Beauchaine and Slep 2018 ). However, this approach limited the extent to infer causal order (Weeland et al 2018 ). Furthermore, victimization was measured with only one item.…”
Section: Discussionmentioning
confidence: 99%
“…This time point was analyzed because the interest was in changes in modeling and reinforcement which were expected immediately after the intervention rather than between post and follow-up measurements (Beauchaine and Slep 2018 ). However, this approach limited the extent to infer causal order (Weeland et al 2018 ). Furthermore, victimization was measured with only one item.…”
Section: Discussionmentioning
confidence: 99%
“…Parenting behavior is therefore theorized to be the most important mechanisms of change. However, empirical studies have not consistently demonstrated that parenting behavior is indeed the key mediator of BPT effectiveness (Forehand et al, 2014; Weeland et al, 2018; Weeland, Chhangur, Jaffee, et al, 2017). Theoretically this can be explained by the fact that the relation between parenting practices and child behavior is neither direct nor unidirectional (Pettit & Arsiwalla, 2008).…”
Section: Behavioral Parent Trainingmentioning
confidence: 99%
“…Theoretically this can be explained by the fact that the relation between parenting practices and child behavior is neither direct nor unidirectional (Pettit & Arsiwalla, 2008). The putative mechanisms of change underlying interventions targeting parenting and child behavior may therefore also be complex (Burke & Loeber, 2016; Kazdin, 2007; Rimestad et al, 2017; Weeland et al, 2018). Changes in parenting and child behavior after participation in BPT may partly be explained by third variables, which often may not be assessed in research on BPT effectiveness.…”
Section: Behavioral Parent Trainingmentioning
confidence: 99%
“…This is consistent with clinical impressions from parenting groups, where parents often report feeling rewarded by success in early home practice assignments, for example seeing their child's pleasure during responsive play. These change processes cannot be captured by traditional mediation models that assume a period of change in parents first, before change in children starts (Weeland et al, 2018a, 2018b). Instead, we hypothesized the existence of subgroups of families with different patterns of co-occurring change, or lack thereof, in children's conduct problems and maternal depressive symptoms.…”
Section: Children's Conduct Problems and Maternal Depressive Symptomsmentioning
confidence: 99%